Retraction Statement: Recognition v. Disclosure, Auditor Tolerance for Misstatement, and the Reliability of Stock‐Compensation and Lease Information (Journal of Accounting Research, 2015)
The above article, published online on March 27, 2006 in Wiley Online Library ( wileyonlinelibrary.com ), has been retracted by agreement between the authors Robert Libby and Mark W. Nelson, the journal Editors, Ray Ball, Philip Berger, Christian Leuz, Haresh Sapra and Douglas Skinner, The Accounting Research Center at the University of Chicago Booth School of Business, and Wiley Periodicals Inc. After receiving notice of Bentley University's report on Dr. James E. Hunton (available at https://www.bentley.edu/files/Hunton%20report%20July21.pdf ), the Editors contacted the authors for additional information to help establish the validity of data that form the basis for this article. Additionally, the Editors and authors received additional information from Bentley University that relates specifically to this paper. The following retraction request was submitted by two of the three authors, Robert Libby and Mark Nelson: “Bentley University conducted an investigation finding that Dr. J.E. Hunton had, while a member of the Bentley University faculty and without the knowledge of his co‐authors, engaged in scientific misconduct [in relation to two published articles]. Dr. Hunton gathered the data used in this study. Therefore, we conclude that the validity of the data underlying the experimental results is in doubt or at least cannot be confirmed, and request that this article be retracted.” Through his counsel, Dr. Hunton contends that the data are valid and disagrees with the coauthors’ request to voluntarily retract the article. However, Dr. Hunton has not responded to our requests for information that would help confirm the validity of the data. Accordingly, two of the three authors have concluded that the validity of the data underlying the experimental results cannot be confirmed. The Editors consider the authors’ statements, taken together, to be sufficiently clear evidence that the findings in this paper are in doubt because the validity of the underlying data cannot be confirmed. We therefore accept Dr. Libby's and Dr. Nelson's request that this paper be retracted and acknowledge Dr. Hunton's objection, through his counsel, to the retraction. REFERENCE Libby , R .; M. W. Nelson ; and J. E. Hunton . “.” Journal of Accounting Research 44 ( 2006 ): 533 ‐ 60 . doi: 10.1111/j.1475-679X.2006.00210.x